Treatment of Cardiovascular Disease in Rheumatoid Arthritis: A Complex Challenge with Increased Atherosclerotic Risk - Saba Ahmed; Benna Jacob; Steven E. Carsons; Joshua De Leon; Allison B. Reiss (MDPI AG, 2021)
Rheumatoid arthritis (RA) carries significant risk for atherosclerotic cardiovascular disease (ASCVD). Traditional ASCVD risk factors fail to account for this accelerated atherosclerosis. Shared inflammatory pathways are fundamental in the pathogenesis of both diseases. Considering the impact of RA in increasing cardiovascular morbidity and mortality, the characterization of therapies encompassing both RA and ASCVD management merit high priority. Despite little progress, several drugs discussed here promote remission and or lower rheumatoid disease activity while simultaneously conferring some level of atheroprotection. Methotrexate, a widely used disease-modifying drug used in RA, is associated with significant reduction in cardiovascular adverse events. MTX promotes cholesterol efflux from macrophages, upregulates free radical scavenging and improves endothelial function. Likewise, the sulfonamide drug sulfasalazine positively impacts the lipid profile by increasing HDL-C, and its use in RA has been correlated with reduced risk of myocardial infraction. In the biologic class, inhibitors of TNF-α and IL-6 contribute to improvements in endothelial function and promote anti-atherogenic properties of HDL-C, respectively. The immunosuppressant hydroxychloroquine positively affects insulin sensitization and the lipid profile. While no individual therapy has elicited optimal atheroprotection, further investigation of combination therapies are ongoing.